Phenotypic and Genotypic Diversity of the Tomato Germplasm From the Lazio Region in Central Italy, With a Focus on Landrace Distinctiveness - Farinon, Barbara; Picarella, Maurizio E.; Siligato, Francesca; Rea, Roberto; Taviani, Paola; Mazzucato, Andrea (Frontiers in Plant Science, 2022)
Italy is a recognized secondary center of diversification for cultivated tomato (Solanum lycopersicum L.). The study of phenotypic and genetic diversity in landrace collections is important for germplasm conservation and valorization. Here, we set up to study the tomato germplasm collected in the region of Lazio in Central Italy, with a focus on the distinctiveness among landraces and the attribution of membership to unnamed accessions. Our regional collection included 32 accessions belonging to eight different locally recognized landraces and 19 unnamed accessions. All accessions were gathered from local farmers and are preserved in the collection held at the Regional Agency for the Development and Innovation of Agriculture in Lazio (ARSIAL) and at the University of Tuscia. We included 12 control genotypes comprising nine landraces from neighbor regions and four reference cultivars. The collection showed wide phenotypic variability for several qualitative and quantitative traits, such as leaf border and shape, inflorescence type, fruit shape, green shoulder, fruit weight (range 14-277 g), locule number (2-12), shape index (0.54-2.65), yield (0.24-3.08 kg/plant), and soluble solids (3.4-7.5 °B). A few landraces showed uncommon phenotypes, such as potato leaf, colorless fruit epidermis, or delayed ripening. Multivariate analysis of 25 cardinal phenotypic variables separated the accessions into two distinct groups; accessions showing a flattened-ribbed fruit were distinguished from those with round to elongate fruits with smooth structure. Genotyping analysis of 7,720 SNPs was performed using the tomato array platform SolCAP, to point out the genetic relationship among the studied accessions. A Neighbour-joining tree analysis allowed to confirm or deny phenotypic data and to assign some of the unnamed accessions to recognized groups. Allelic status at marker loci linked to resistance genes commonly used in breeding identified accessions putatively derived from modern material or commercial hybrids, thus not classifiable as landraces. Overall, this study provided information useful to preserve, valorize, and juridically protect tomato local landraces from the Lazio region and will in addition be helpful to their improvement by breeding.